The Paris apartment - Bowen, Kelly (Romance fiction writer) (Forever, 2021)
"London, 2017: When Aurelia Leclaire inherits an opulent Paris apartment, she is shocked to discover her grandmother's hidden secrets--including a treasure trove of famous art and couture gowns. One obscure painting leads her to Gabriel Seymour, a highly respected art restorer with his own mysterious past. Together they attempt to uncover the truths concealed within the apartment's walls. Paris, 1942: The Germans may occupy the City of Lights, but glamorous Estelle Allard flourishes in a world separate from the hardships of war. Yet when the Nazis come for her friends, Estelle doesn't hesitate to help those she holds dear, no matter the cost. As she works against the forces intent on destroying her loved ones, she can't know that her actions will have ramifications for generations to come. Set seventy-five years apart, against a perilous and a prosperous Paris, both Estelle and Lia must unearth hidden courage as they navigate the dangers of a changing world, altering history-and their family's futures-forever."--